2018
DOI: 10.5946/ce.2018.012
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study to Develop a Method for Improving Sample Collection to Monitor Laryngoscopes after Reprocessing

Abstract: Background/AimsThe microbiological surveillance of endoscopes and automated flexible endoscope reprocessing have been proven to be two of the most difficult and controversial areas of infection control in endoscopy. The purpose of this study was to standardize a sampling method for assessing the effectiveness of standard reprocessing operating procedures for flexible fiberoptic laryngoscopes (FFLs). MethodsFirst, the sampling devices were directly inoculated with Bacillus atrophaeus spores; second, tissue non … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…In our study, we adopted TNT wipes, a more efficient device for sampling surfaces that could improve the accuracy and reproducibility of environmental surveillance as discussed in a previous study [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we adopted TNT wipes, a more efficient device for sampling surfaces that could improve the accuracy and reproducibility of environmental surveillance as discussed in a previous study [12].…”
Section: Discussionmentioning
confidence: 99%
“…We developed a surface sampling method (by TNT wipes) to detect low levels of bacteria on a FFNs as discussed in a recent publication [12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sampling method needs to be further defined and clarified. In this issue of Clinical Endoscopy , Ditommaso et al published a study on the efficacy of a surface sampling device for surveillance culture after flexible fiberoptic laryngoscopes [ 7 ]. In this study, the extraction efficiency of three different sampling devices (tissue non tissue [TNT] wipes, cellulose wipes, and hydrated sponge) inoculated with Bacillus atrophaeus spores were compared and TNT wipes showed the highest extraction efficiency (93% vs. 52% and 49%, respectively).…”
mentioning
confidence: 99%
“…Surveillance sampling and culturing of endoscopes are a major concern to prevent iatrogenic infection in patients during endoscopic procedures. Surface sample culture of endoscopes was not demonstrated to be much better than channel flushing/brushing or endoscope tip swabbing, but an experimental study by Ditommaso et al called attention to surface sample culture and showed the superiority of the TNT wipes in terms of extraction rate [ 7 ]. More research studies are needed, and appropriate standards should be prepared to apply this study results in clinical practice.…”
mentioning
confidence: 99%